Pertumbuhan Tanaman Sawi Hijau (Brassica juncea L.) dengan Pemberian Kompos Berbahan Dasar Daun Paitan (Thitonia diversifolia) - Istarofah Istarofah; Zuchrotus Salamah (BIO-SITE |Biologi dan Sains Terapan, 2017)
This study aimed to determine the growth of mustard green (Brassica juncea L.) by addion Paitan leaves (Tithonia diversifolia) based compost at different doses and to determine the optimum dose of compost. This study used a completely randomized design (CRD) with one factor that is the dose of Paitan leaves based compost and the treatments were: A1 = 0.25 kg of compost, A2 = 0.5 kg of compost, A3 = 0.75 kg of compost, A4 = 1 kg of compost, A5 = 1.25 kg of compost and control (without compost), and each treatment was added by the soil so that the total weight was 2.5 kg in each polybag. Observation parameters were the plant height, leaf number, leaf length, leaf width, wet weight and dry weight of plants. The data were tested with Analysis of Variant (ANOVA) and followed by LSD test at 5% level. Based on the results of this study, it was concluded that the growth of mustard green plant by addition Paitan leaves based compost at various doses showed different growth of plants. the A3 Treatment is the most optimum dose to raise the growth of mustard green.